Growth evolution of self-textured ZnO films deposited by magnetron sputtering at low temperatures - Bortoleto, José Roberto Ribeiro [UNESP]; Chaves, Michel [UNESP]; Rosa, Andressa Macedo; Silva, Erica Pereira da [UNESP]; Durrant, Steven Frederick [UNESP]; Trino, Luciana Daniele [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP] (Elsevier B.V., 2015)
In this work, the evolution of the surface morphology of ZnO thin films deposited by reactive RF magnetron sputtering has been investigated using atomic force microscopy (AFM) and X-ray diffraction (XRD). All AFM images of the films were analyzed using scaling concepts. To study the growth evolution, different ZnO films with thicknesses of up to 1270nm were deposited at temperatures of 100 and 250 degrees C. For the films grown at 100 degrees C, AFM data show that the lateral length xi evolves continuously while the temporal evolution of the root mean square roughness sigma presents two distinct regimes. Early during the depositions, the morphology of the ZnO films is mainly characterized by granular structures. Beyond thickness of about 600nm, pyramid-like structures with {214} crystallographic facets start to develop. For the films grown at 250 degrees C, however, only one growth regime was observed and for the thicker films, the surface morphology consisted of polygonal structures. For the films grown at 100 degrees C, the growth exponents beta, and the exponent defining the evolution of the characteristic wavelength of the surface, p, were beta(1) = 0.70 +/- 0.02 and beta(2) = 0.26 +/- 0.2; and p = 0.2 +/- 0.04. For the films grown at 250 degrees C, the exponent values were beta = 0.78 +/- 0.02 and p = 0.32 +/- 0.05. These values of the exponents indicate the occurrence of surface mechanisms, such as shadowing and surface diffusion, as well as facet stabilization at 100 degrees C. For the films grown at 250 degrees C, however, structural misorientation during growth also plays an important role.
Keywords: Surface texturing; ZnO thin films; Magnetron sputtering; Low temperature; Growth evolution